Predicted toxicity of naphthenic acids present in oil sands process-affected waters to a range of environmental and human endpoints - Scarlett, Alan; West, C.; Jones, D.; Galloway, T.; Rowland, S. (2012)
Naphthenic acids (NAs) are considered to be a major toxic component of oil sands process-affected waters (OSPW) and are also widely used for industrial processes. The effects of previously identified NAs (54 in total), together with six alkylphenols, were modelled for a range of environmental and human toxicity related endpoints using ADMET predictor™ software. In addition to the models, experimental CALUX® assays were performed on seven tricyclic diamondoid acids. Most of the NAs modelled were predicted to have lethal median concentrations (LC50) >100µM for the three aquatic species modelled. Polycyclic acids containing a single aromatic ring were predicted to be the most toxic to fathead minnows with LC50s typically ca 1µM. Some of these compounds were also predicted to be the most carcinogenic (based on rat and mouse models), possess human estrogenic and androgenic activity and potentially disrupt reproductive processes. Some aliphatic pentacyclic acids also were predicted to exhibit androgenic activity and, uniquely amongst the compounds tested, act as substrates for the cytochrome P450 enzyme CYP3A4. Consistent with the models' predictions for the tricyclic acids, no estrogenic or androgenic activity was detected by ER/AR CALUX®. Further experimental validation of the predictions should now be performed for the compounds highlighted by the models (e.g. priority should perhaps be focused on the polycyclic monoaromatic acids and the aliphatic pentacyclic acids). If shown to be accurate, these compounds can then be targeted for toxicity reduction remediation efforts. © 2012 Elsevier B.V.